Human Capital Investment: Building an App for That - Ross, Matthew M.; Wright, A. Michelle; Peffers, Simon N. (Journal of Applied Business and Economics, 2021)
This paper outlines the development of a prototype application to estimate the human capital investment of education-career selections. We explain the need to deliver the right information, to the right person, at the right time using a customizable, individualized, just-in-time format. We illustrate how a collaboration between academia and FinTech might leverage the power of distributed expertise to support human capital investment planning via robo-advising. With 112 research-based default parameters, the application can provide detailed financial estimates in seconds. The prototype includes an interface to customize 12 key parameters allowing for extensive exploration of career and education pathways. We illustrate technical elements, the complexity of comprehensive personal financial projections, psychological obstacles, the potential for agency conflict, and balancing academic rigor with user experience. We also offer some insight into challenges and opportunities of this pre-seed venture.